Stability of the Carboniferous Slate along the Ljubljana - Celje Highway from the Petrographic Point of View - Trajanova, Mirka (Geologija, 2001)
The Carboniferous clastic rocks along the highway from Ljubljana passing across the Trojane hilly area toward Celje belong predominantly to shale and subordinate sandstone, forming laminas, layers and also thicker sandstone intervals. They have been dynamometamorphosed to the anchizone grade to slates and weakly metamorphosed sandstones. Primary and newly developed anisotropies together with mineral composition and secondary fracturing resulted geomechanically into a very unstable rock, sensitive primarily to the shear strain. The laboratory shear tests show failures along existing anisotropies in the rock.